Social brain: Evolution - Dunbar, R (Elsevier, 2010)
Increases in brain size within different mammalian lineages, and in particular increases in neocortex volume within primates, appear to be associated with shifts to more intense forms of sociality. In primates, this is reflected in a strong correlation between neocortex volume and social group size, as well as in correlations with various behavioral indices of social complexity. This relationship seems to be underpinned by cognitive abilities such as the theory of mind, which, while specialized for social tasks, may nonetheless be the emergent properties of more fundamental cognitive abilities associated with executive functions. As a result, there is some evidence to suggest that the frontal lobe may play a disproportionate role in managing social skills. © 2009 Elsevier Ltd All rights reserved.